Efektivitas Penggunaan Telehealth Guna Meningkatkan Kualitas Hidup bagi Pasien Layanan Fisioterapi di RS Efarina Berastagi - Fujastawan, I Ngurah Gede Verar; Herawati, Noni; Lumbantoruan, Ruth Mala Livia Theola (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2025)
Along with the times, the use of information and communication technology is also applied in the field of health, especially physiotherapy. Telehealth is one of the services offered to overcome problems such as difficult access to Physiotherapy services, limited costs and transportation, as well as pandemic conditions that do not allow to conduct therapy directly. To find out the effectiveness of telehealth use in Physiotherapy services. Conducted a critical review on eight selected Randomized Controlled Trial (RCT) articles, provided Quartile articles 1 and 3. Telehealth services can be an alternative option for individuals who are less able to access conventional services. The effectiveness of telehealth use can be seen through many things such as adequate regional conditions, internet network connections, age factors and understanding of patients using telecommunications equipment, as well as cases of disease suffered. Based on the results of critical review studies of eight selected articles, telehealth services are effectively used and can be an alternative option in conducting real-time interactions anywhere and anytime.